Development of New Anpr Dataset for Automatic Number Plate Detection and Recognition in North of Iraq - Yaseen, Naaman Omar; Al-Ali, Salim Ganim Saeed; Sengur, Abdulkadir (Institute of Electrical and Electronics Engineers Inc., 2019)
An automatic number plate detection (ANPD) and automatic number plate recognition (ANPR) systems are robust technologies that are used for detecting and recognizing the number plates of vehicles. In this paper, a new dataset, which is called North Iraq-Vehicle Images (NI-VI) of three provinces (Duhok, Erbil, and Sulaimani) for vehicle images, is presented. There are 1500 images in this dataset. They were gathered from real-time by using handled cameras to form a realistic dataset of the vehicle images. The main contribution of this work is the creation of a new dataset for license plate of vehicles in north Iraq with Arabic fonts in different and difficult conditions. The dataset includes three categories of images: rotated, scaled and translated images. The resolutions of images are 4288 x 2848 and 5184 x 3456. Moreover, some images created for bad weather conditions, such as snowy, dusty and low lighting. Some dirty plate images also considered in the dataset. The purpose of introducing this dataset is to provide and produce a realistic dataset for ANPD and as well as for ANPR systems. © 2019 IEEE.
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: and License number detection datasets; Automatic number plate detection (ANPD) datasets; Automatic number plate recognition (ANPR) datasets; Plate number recognition datasets